Dynamics of heat and mass transfer: Ree-Eyring nanofluid flow over a Riga plate with bioconvention and thermal radiation - Loganathan, K.; Alessa, Nazek; Jain, Reema; Ali, Farhan; Zaib, Aurang (Frontiers in Physics, 2022)
The flow of Ree-Eyring nanofluid over a Riga plate in the presence of radiation is examined in this investigation. The movement of motile microorganisms stabilizes the nanoparticle distribution in the nanofluid, which is known as bioconvection. Along with the convective boundary condition, the influence of thermophoresis and Brownian motion, which are crucial in the movement of heat and mass, is taken into account. Non-Newtonian nanofluid flow is widely used as a key element of cooling in a variety of manufacturing industries. Additionally, it has uses in biomedical engineering, cancer treatment, thermal extrusion systems, etc. Based on these assumptions, the governing equations are constructed using partial differential equations that are then converted into non-linear differential equations using the relevant relations. These nonlinear differential equations are solved using the Homotopy Analysis Method (HAM), and the solutions are displayed in graphs for distinct fluid flow parameters. The coefficient of skin friction increases as the mixed convection parameter values rise, and the opposite effect is seen as the bio-convection Rayleigh number grows.